Peran Kecerdasan Spiritual Terhadap Generasi yang Dipulihkan - Saronisa Ginting (Sekolah Tinggi Teologi Baptis Medan, 2022)
AbstractAlong with the times and advances in science, affects various aspects of human life. On the one hand, with the advancement of human civilization, the realization of a modern human, a prosperous life, and facilities in several ways/fields. Spiritual intelligence means intelligence related to the psyche, mind, and instincts, while the restored generation is the generation that has managed to win over the negative effects of the times and become influencers. This article discusses the role of Spiritual Intelligence in the Restored Generation. Where will be discussed in several subtitles, namely 1) Spiritual Intelligence (Spiritual Quotient, the definition of spiritual intelligence, restored generation, recovered generation from temptation and challenges of depravity (Proverbs 7: 7); 4) The Role of Spirituality in the Restored Generation (Psalm 119: 9); The Restored Generation can Become a Source of Inspiration (1 Timothy 4:12), and the conclusion is that spiritual intelligence is a must-have for everyone, the virtue of spiritual intelligence is to form the correct attitude and perspective towards all aspects of life, a person who has a spiritual intelligence who well in Christ, of course, the wisdom and outlook on life will be more than anything else Keywords: intelligence, spiritual, generations, restored AbstrakSeiring perkembangan zaman dan kemajuan IPTEK, mempengaruhi berbagai aspek pada kehidupan manusia. Disatu sisi dengan kemajuan peradaban manusia terwujudnya manusia yang modern kehidupan yang sejahtera serta kemudahan-kemudahan dalam beberapa hal/ bidang. Kecerdasan spiritual berarti kecerdasan yang berkaitan dengan kejiwaan, batin, dan naluri, sedangkan generasi yang dipulihkan yaitu generasi yang berhasil menang dari dampak negatif zaman dan menjadi pemberi pengaruh. Artikel ini membahas tentang peran Kecerdasan Spiritual Terhadap Generasi yang Dipulihkan dalam beberapa sub judul yaitu Kecerdasan spiritual (spiritual quotient, defenisi kecerdasan spiritual, generasi yang dipulihkan, generasi yang dipulihkan dari godaan dan tantangan kebobrokan (Amsal 7:7); Peran spiritualitas terhadap generasi yang dipulihkan (Mazmur 119:9); generasi yang dipulihkan dapat menjadi sumber inspirasi (1 Timotius 4:12), dan kesimpulannya bahwa kecerdasan spiritual wajib dimiliki oleh setiap orang, keutamaan dalam kecerdasan spiritual adalah untuk membentuk sikap dan cara pandang yang benar terhadap segala aspek kehidupan, seseorang yang memiliki kecerdasan spiritual yang baik didalam Kristus, tentunya hikmat dan pandangan hidup yang dimiliki akan melebihi apapun Kata Kunci: kecerdasan, spiritual, generasi, dipulihkan